2015
DOI: 10.1245/s10434-014-4339-5
|View full text |Cite
|
Sign up to set email alerts
|

Modern Treatment of Rectal Cancer Closes the Gap Between Common Adenocarcinoma and Mucinous Carcinoma

Abstract: Modern treatment of RC has benefited MC patients, leading to equal survival for MC and AC patients. Enhancements in the fields of imaging and quality of surgery have improved outcome and preoperative therapies should be recommended for both histological subtypes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
37
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(42 citation statements)
references
References 42 publications
2
37
2
1
Order By: Relevance
“…The latter is in accordance with a recent study from our group that reported on outcomes in LARC patients with mucinous AC and AC. This study demonstrated that pCR was not observed in any mucinous AC patient compared with over 16 % in AC patients, which did not affect survival 29. In the current cohort, pCR rates were again significantly lower in mucinous AC patients without an effect on OS.…”
Section: Discussionsupporting
confidence: 41%
“…The latter is in accordance with a recent study from our group that reported on outcomes in LARC patients with mucinous AC and AC. This study demonstrated that pCR was not observed in any mucinous AC patient compared with over 16 % in AC patients, which did not affect survival 29. In the current cohort, pCR rates were again significantly lower in mucinous AC patients without an effect on OS.…”
Section: Discussionsupporting
confidence: 41%
“…Some researchers tried to ascribe this poor PRT response to radiation resistance. Hugen N et al 16. found that mutated KRAS as a biomarker was strongly associated with poor response to chemoradiotherapy in MC.…”
Section: Discussionmentioning
confidence: 99%
“…Many oncologists considered RC patients with stage II–III as an indication for preoperative radiotherapy (PRT), and recommend to add chemotherapy for patients with locally advanced RC in which the mesorectal fascia is threatened41415. The efficacy of neo-adjuvant therapy including PRT for RC has been described in many literatures161718. SRCC was prone to extensive lymphatic spread and peritoneal metastases leading to poor survival.…”
mentioning
confidence: 99%
“…In some of the patients, however, MLs are induced by nCRT in rectal cancer tissue (5)(6)(7)(8)(9)(10)(11)(12). In patients who receive nCRT, the incidence of mucinous carcinoma is relatively high, ranging from 13% to 24% (6,8,11).…”
Section: Discussionmentioning
confidence: 99%
“…Patients with mucinous carcinoma have been reported to have a poor response to nCRT, as well as poor outcomes. In some patients, however, nCRT may induce the formation of mucin lakes (MLs) in rectal cancer tissue (5)(6)(7)(8)(9)(10)(11)(12). The ability to determine whether MLs are induced or originally exist in resected specimens would be of great clinical significance.…”
mentioning
confidence: 99%